Tunable SERS Platforms from Small Nanoparticle 3D Superlattices: A Comparison between Gold, Silver, and Copper. Issue 21 (4th October 2017) - Chapus, Lionel; Aubertin, Pierre; Joiret, Suzanne; Lucas, Ivan T.; Maisonhaute, Emmanuel; Courty, Alexa
Abstract: Herein we present new substrates for surface‐enhanced Raman spectroscopy (SERS). The synthesis of colloidal nanoparticles through an organometallic route allowed us to obtain gold, silver, or copper nanoparticles with well‐controlled shapes and sizes (5–12 nm in diameter). The organization of these nanoparticles into large‐scale 3D superlattices produces a very large number of "hot spots" at the origin of the signal enhancement. Each superlattice was studied individually to correlate its optical and SERS properties to the thickness, the nanoparticle sizes, and the interparticle distance. This experimental and theoretical study provides insights for the optimization and tuning of the SERS activity. Indeed, significant SERS amplification could be observed regardless of the nature of the metal. In addition, the SERS signal was homogeneous at the surface of the superlattices, which opens the route for a new approach in analytical SERS detection. Abstract : Lattices for enhancement : Self‐organized small metallic nanoparticles present exceptional optical and surface‐enhanced Raman spectroscopy (SERS) responses that depend on the superlattice thickness.